Respuesta :
Respuesta:
[tex] \frac{1}{2} + \frac{6}{7} = \frac{12 + 7}{14} = \frac{19}{12} [/tex]
[tex] \frac{2}{5} + \frac{7}{8} = \frac{35 + 16}{40} = \frac{51}{40} [/tex]
[tex] \frac{3}{4} + \frac{1}{8} = \frac{4 + 24}{32} = \frac{28}{32} = \frac{7}{8} [/tex]
[tex] \frac{9}{4} - \frac{4}{7} = \frac{63 - 16}{28} = \frac{47}{28} [/tex]
[tex] \frac{2}{3} + \frac{5}{7} = \frac{14 + 15}{21} = \frac{29}{21} [/tex]
[tex] \frac{3}{10} - \frac{1}{12} = \frac{18 - 5}{60} = \frac{13}{60} [/tex]
[tex] \frac{5}{6} + \frac{1}{4} = \frac{6 + 20}{24} = \frac{26}{24} = \frac{13}{12} [/tex]
[tex] \frac{2}{4} + \frac{9}{2} = \frac{4 + 36}{8} = \frac{40}{8} = 5[/tex]
[tex] \frac{2}{3} - \frac{2}{5} = \frac{10 - 6}{15} = \frac{4}{15} [/tex]